Pengaruh Profitabilitas dan Leverage terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Consumer Non-Cyclical yang Terdaftar di Bursa Efek Indonesia Periode 2021–2024 - Agis Nuraeini; Hania Setiana; Hilda Aini Lutfiah; Regita Cahyani (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2026)
The purpose of this study is to examine the impact of profitability and Leverage on the firm value of manufacturing companies operating in the Non-Cyclical consumer goods sector and listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employs a quantitative methodology using secondary data extracted from the annual financial reports published by these companies. The research sample consists of 32 companies with a total of 128 observations selected using purposive sampling. Data analysis was conducted using panel data regression with the Random Effects Model (REM). The findings indicate that profitability, as measured by ROA, has a positive and statistically significant effect on firm value (PBV), while Leverage (DER) does not show a significant impact. Furthermore, when analyzed together, profitability and Leverage do not produce a significant effect on firm value. These results indicate that investors prioritize a firm’s ability to generate profits over its debt level when assessing firm value.